2002
DOI: 10.1046/j.1537-2995.2002.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

RHC and RHc genotyping in different ethnic groups

Abstract: Reliable RHC and RHc genotyping is possible in different ethnic groups with the RHC/c/hex3-intron 4/exon 7 multiplex PCR approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 32 publications
2
41
0
3
Order By: Relevance
“…The results obtained after analysis of sample 1 confirmed that it is not possible to obtain accurate RhC/c results by testing the RHCE nucleotide 48 polymorphism alone. This polymorphism does not correlate with the RhC/c phenotype, particularly in the Dce haplotype [10,11].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The results obtained after analysis of sample 1 confirmed that it is not possible to obtain accurate RhC/c results by testing the RHCE nucleotide 48 polymorphism alone. This polymorphism does not correlate with the RhC/c phenotype, particularly in the Dce haplotype [10,11].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…However, because different ethnic groups have different genetic background and especially numerous variant RHCE alleles, many DNA genotyping techniques were found not reliable. Tax et al [23] mentioned that RHCE*C genotyping based on 48C was not reliable because of a 48G>C mutation in the RHCE*ce allele (false-positive prediction of C), and genotyping on intron 2 is unreliable because of r's (Cdes) alleles (false-negative prediction of C). Then, in France, Pham et al [24] and Kappler-Gratias et al [25] reported 572/806 individuals and 14.2% African blood donors, respectively, with RhCE variants or variant RHCE alleles.…”
Section: Discussionmentioning
confidence: 99%
“…Exons 2 of RHD and RHCE * C have an identical sequence, so it is not possible to design allele -specifi c primers for identification of RHCE * C (except in D − samples), though it is relatively straightforward to design them for RHCE * c [128,318,321] . Exons 2 of RHD and RHCE * C have an identical sequence, so it is not possible to design allele -specifi c primers for identification of RHCE * C (except in D − samples), though it is relatively straightforward to design them for RHCE * c [128,318,321] .…”
Section: Predicting C/c Phenotype From Dnamentioning
confidence: 99%